Replacing Soybean Meal with Soy Protein Concentrate in Diets Containing 12% Crude Protein Does Not Maintain Performance in Finishing Pigs from 240 to 280 lb - J. A. Soto; M. D. Tokach; S. S. Dritz; J. C. Woodworth; J. M. DeRouchey; R. D. Goodband (Kansas Agricultural Experiment Station Research Reports, 2018)
A total of 252 pigs (DNA 600 × 241, initially 238.8 lb) were used in a 21-d trial to determine the effects of replacing soybean meal (SBM) with soy protein concentrate (SPC) in diets containing 12% crude protein (CP) on growth performance of finishing pigs from 240 to 280 lb. Pens of 7 or 8 pigs were allotted by body weight (BW) and randomly assigned to 1 of 4 dietary treatments with 8 replications per treatment. Treatments consisted of 3 levels of SBM (10.6, 5.3, and 0%) with 12% CP and a negative control treatment with 4.0% SBM and 10% CP. Soy protein concentrate was increased as SBM decreased to maintain 12% CP. For overall growth performance, decreasing SBM marginally decreased (linear,P= 0.062) average daily gain (ADG) and worsened (linear,P= 0.061) feed efficiency (F/G). In conclusion, regardless of the 12% CP level, reducing the concentration of SBM and replacing it with SPC worsened ADG and F/G.
Keywords: soybean meal; crude protein; finishing pigs